Assessment of Hydrodynamic Cavitation Technology to Treat the Leachate Resulting from Wadi Al-Hada Facility in Tartous City - جنيدي حسين; داود علي; سليمان آلاء (Latakia University Journal -Engineering Sciences Series, 2020)
In this research, the leachate, which generated from the composting process of municipal waste sorting plant in Wadi Alhada in Tartous, has been studied. The waste in the plant is subject to mechanical screening, and the organic part of it is treated biologically through the process of composting. This process generates a leachate, which the rainfalls increase their quantity. The leachate contains very high concentrations of organic and inorganic substances and heavy metals, and in view of its danger to the soil and water of the region, in order to be treated, it was described through quarterly samples, and the following indicators were determined :(COD، BOD5، NO3- ، PO4-3 ،pH، TDS، EC). The maximum value of COD and BOD5, respectively, was 65000، 44000 mgO2/l. Given the nature of the leachate and its contaminants, the hydrodynamic cavitation technique (HDC) was selected with a view to reducing the organic load and destroying its complex organic compounds, thus preparing them for subsequent treatments. The removal efficiency of the COD was 33.33% achieved after (135) minute of cavitation time, whereas, no change was observed for the BOD5 indicator. The results showed that the method (HDC) is effective for the primary treatment of the leachate, leading to greater efficiency in subsequent treatments with a reduction in time and economic costs.